Intervention to severe lower trachea obstruction supported by extracorporeal membrane oxygenation in a human immunodeficiency virus patient: A case report and literature review - Zhang, Xiaolin; Pan, Lei; Wang, Lei; Li, Li Q.; Zhang, Peng; Tang, Hai C.; Wu, Qing G.; Li, Feng (Frontiers in Medicine, 2022)
Here we reported a case, male, 33 years old, diagnosed with HIV infection 4 years ago, but he didn`t take antiretroviral drugs regularly. He was admitted to intensive care unit emergently due to hypoxemia, hypercapnia, and hypotension. Throat CT showed severe lower trachea obstruction caused by soft tissue. After rapid bedside assessment, the patient was considered to need endotracheal operation, but he couldn`t tolerate intubation and mechanical ventilation. Extracorporeal membrane oxygenation (ECMO) was used. Hemodynamics improved significantly along with rehydration and low-dose vasoactive drugs. Subsequently, the patient underwent rigid bronchoscopy, airway tumor resection and Y-type silicone stent implantation. Postoperatively protective endotracheal intubation and mechanical ventilation was followed. ECMO was weaned off after the operation, and endotracheal cannula was removed 6 hours later. The pathological examination of excisional tissue showed lung squamous cell carcinoma. The patient was discharged 3 days after the operation and went to local hospital for further treatment. From this case, we conclude that ECMO could play a key role for those who need endotracheal surgery while cannot endure conventional intubation and mechanical ventilation.